Access to Mainstream Microfinance Services for Persons with Disabilities – Lessons Learned from Uganda - Flavia Nakabuye Bwire; George Mukasa; Roy Mersland (Disability Studies Quarterly, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:NO-BOK; mso-fareast-language:NO-BOK; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>This article reports from a pilot project in Uganda where the aim is to enable persons with disabilities to have access to mainstream microfinance services. Several lessons have already been learned: 1) entrepreneurs with disabilities are an untapped market opportunity for Micro Finance Institutions (MFIs); 2) to influence MFIs it is important to understand their business model and team up with key actors from the industry; 3) persons with disabilities are often misinformed about MFIs’ terms and services and don’t know how to tap these opportunities. Gradually a change in attitudes in MFIs and Disabled Peoples Organizations (DPOs) is observed. All MFIs participating in the project now report an increase in the number of clients with disabilities served. This is happening without the use of any economic incentives.
Keywords: Microfinance; disability; Uganda; mainstreaming; inclusion efforts.